PENINGKATAN HASIL BELAJAR TEMATIK TERPADU MENGGUNAKAN MODEL ASSURE SISWA KELAS V SD SWASTA PELITA MEDAN - Muliana Muliana; Regina Frederika Sipayung (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to improve the integrated thematic learning outcomes of Class V students of SD Swasta Pelita Medan using the ASSURE model. This research is a Classroom Action Research (PTK) with 2 cycles and 2 meetings in each cycle. The subjects of this study were 33 fifth grade students of SD Swasta Pelita Medan. Data were collected through observation sheet of learning design implementation, learner response questionnaire, and student activity observation sheet during the learning process and student learning outcomes. The data obtained were processed and analysed descriptively. The conclusion of the research shows that the correct use of the ASSURE model can improve the learning outcomes of Theme 8 students in Class V of SD Swasta Pelita Medan, it appears that the results of cycle I obtained a score of 79.75 and cycle II obtained 92.42.